2010
DOI: 10.1093/annonc/mdq035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of rituximab to salvage chemotherapy on outcome of patients with diffuse large B-cell lymphoma relapsing after an autologous stem-cell transplantation

Abstract: The addition of rituximab to salvage chemotherapy improves response rates and EFS in patients with relapsed DLBCL after ASCT. These patients may benefit from rituximab retreatment, although larger prospective studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…In the present patient, we assumed that relapse of aggressive lymphoma after autologous peripheral blood stem cell transplantation may lead to a poor prognostic course. 8,9 Contrary to our expectations, the orbital relapse was proven as MALT lymphoma. PET/CT demonstrated abnormal uptake sites in lymph nodes, in addition to the orbital lesion, indicating systemic involvement with lymphoma.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In the present patient, we assumed that relapse of aggressive lymphoma after autologous peripheral blood stem cell transplantation may lead to a poor prognostic course. 8,9 Contrary to our expectations, the orbital relapse was proven as MALT lymphoma. PET/CT demonstrated abnormal uptake sites in lymph nodes, in addition to the orbital lesion, indicating systemic involvement with lymphoma.…”
Section: Discussioncontrasting
confidence: 78%
“…6,7 Further relapse after hematopoietic stem cell transplantation has been understood as a poor prognostic sign in lymphoma treatment. 8,9 Recently, high-dose chemotherapy and autologous stem cell transplantation have been evaluated as a first-line therapy for aggressive nonHodgkin lymphoma with poor prognostic indicators. [10][11][12] In this study, we report a patient who developed orbital MALT lymphoma after autologous peripheral blood stem cell transplantation for follicular lymphoma as the relapse of diffuse large B-cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study from Memorial Sloan‐Kettering Cancer Center showed a median survival time of 7·7 months in 66 of 139 patients with chemosensitive relapsed or refractory aggressive NHL who had failed transplant (Kewalramani et al , ). These findings were supported by a retrospective analysis of 82 patients with DLBCL (a third of whom received prior rituximab) demonstrating improved survival following the addition of rituximab to salvage chemotherapy post‐ASCT (Calvo‐Villas et al , ; In an evaluation of 53 relapsed/refractory aggressive B‐cell NHL (primarily DLBCL) patients treated between 1992 and 2007, rituximab maintenance or use in combination salvage treatment ( n = 19) showed significant improvements in PFS (not yet reached with rituximab vs. 29 months for control, respectively; P = 0·002) and OS (not yet reached with rituximab vs. 42 months for control, respectively; P = 0·011) compared with patients receiving no post‐ASCT therapy ( n = 37) (Tsirigotis et al , ). Preliminary findings from the phase III COllaborative trial in Relapsed Aggressive Lymphoma (CORAL) study in DLBCL suggest that it may be difficult for patients with prior exposure to rituximab (in combination with chemotherapy) to respond to salvage rituximab after ASCT (Hagberg & Gisselbrecht, ).…”
Section: Discussionmentioning
confidence: 79%
“…Patients with COO identified as GCB-derived disease have better prognosis compared with patients with non-GCB disease (4). Patients with aggressive forms of NHL, such as DLBCL and transformed follicular lymphoma (TFL), often have a poor prognosis and relapse after firstline treatment with rituximab plus anthracycline-based chemotherapy such as CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) or second-line high-dose chemotherapy with autologous stem cell rescue (5,6). Other types of NHL, such as mantle cell lymphoma (MCL), have had several agents recently approved for use, but despite these new agents, most patients eventually succumb to the disease (7).…”
Section: Introductionmentioning
confidence: 99%